Peningkatan Kemampuan Menulis Laporan Observasi Melalui Model Pembelajaran Kontekstual Pada Siswa Kelas VIII SMPN 85 Jakarta - Sumartin Sumartin (UHAMKA Graduate School Thesis Abstract Collection, 2016)
In accordance with the existing problems , the purpose of this research that is, to know how high increased capacity writing a report through observation kind of classroom contextual students Grade VIII 85 Junior High School of jakarta . Research that is used is the act of research .The act of research is research in the form of measures in the cycle to produce an increase of were being explored. The act of research is that research focus on the series of activities consisting of four measures , including planning ( planning ) , the act of ( action , observation, observing ) , and reflection ( reflecting ) .A subject in this research is a student of Grade VIII 85 Junior High School of jakarta consisting 36 students . On the cycle used i this kind of classroom Contextual in improved the skills of writing a report students Grade VIII 85 Junior High School of jakarta .In I this cycle , only 11 ( eleven ) students who has successfully in accordance with criteria ketuntasan minimum & amp; # 8804; 70 .After doing reflection based on the research cycle I , so disusunlah action plan on cycle ii .Action against cycle II equal to action against cycle I namely use the model learning contextual .In cycles II , can be obtained data that all students increased in accordance criteria minimum, which reached good success 82.29 From the data analysis cycle I until cycle II happened an increase of 14.81 .From the data analysis praintervensi to cycle I happened an increase of 16.32 .